Rural road-induced sedimentation: Severity and local perception in the Phewa Watershed, Kaski District, western Nepal (Journal of Nepal Geological Society, 2013)
The aim of this research is to estimate sediment source and its severity in the Phewa watershed resulted from rural roads construction, and to evaluate local people's perception towards it. A total length 63 km in twenty five rural roads accounts up to 269752 ml of sediments with 4292.00 ml per kilometer in average. Similarly the rural road-induced landslides contribute about 25593 ml sediments with average of I024 ml per landslide. This signifies the severity of sedimentation problem posed by unplanned rural road construction. The people living in the rural road areas have positive responses towards rural transportation and other socio-cultural dimensions. However, it has several negative consequences in relation to conservation of upstream and downstream infrastructures and social values. The amounts of sediments resulting from the road construction and associated landslides are threatening. It warrants for concerted efforts to reduce sediment load by implying environmentally sound construction techniques, policy and process.